2018
DOI: 10.1080/09712119.2018.1469497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of double GnRH injections on reproductive parameters in Awassi ewes receiving long-term progesterone

Abstract: The aim of this study was to investigate the effect of single or double Gonadotropin releasing hormone (GnRH) injections at the time of mating and following on day 9 on pregnancy rates and litter size in ewes. Oestrus was synchronized in 130 adult ewes using intravaginal sponges containing 20 mg of fluorogestone acetate for 14 days. All ewes received 10 IU/kg of pregnant mare serum gonadotropin (PMSG) at the sponge withdrawal. Then animals were divided into three groups. Ewes in group 1 (G1; Control, n = 68) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
2
1
Order By: Relevance
“…In the present study, increase kilogram kids per goats joined in groups B2 and B5 than other groups indicated maintenance of pregnancy that is require elevated progesterone and protect the corpus luteum during early pregnancy and inhibition prostaglandin F2α from uterine by interferon-tau (IFNT) from the elongating embryo (Wiltbank et al, 2018) and accelerate embryonic development and improve pregnancy rates (Nephew et al, 1994). However, the results obtained in this study in group B5 agreement with (Medan et al, 2002;Husein et al, 2005;Zonturlu et al, 2018). In contrast, decrease kilogram kids per goats joined in group B4 was similar to other studies reported (Fonseca et al, 2005;Dias et al, 2018) hCG treated to improve ovulation synchronization and in contrast decrease in the pregnancy rate.…”
Section: Discussioncontrasting
confidence: 65%
“…In the present study, increase kilogram kids per goats joined in groups B2 and B5 than other groups indicated maintenance of pregnancy that is require elevated progesterone and protect the corpus luteum during early pregnancy and inhibition prostaglandin F2α from uterine by interferon-tau (IFNT) from the elongating embryo (Wiltbank et al, 2018) and accelerate embryonic development and improve pregnancy rates (Nephew et al, 1994). However, the results obtained in this study in group B5 agreement with (Medan et al, 2002;Husein et al, 2005;Zonturlu et al, 2018). In contrast, decrease kilogram kids per goats joined in group B4 was similar to other studies reported (Fonseca et al, 2005;Dias et al, 2018) hCG treated to improve ovulation synchronization and in contrast decrease in the pregnancy rate.…”
Section: Discussioncontrasting
confidence: 65%
“…A high oestrous response was obtained with all protocols used in this study as shown by the proportion of ewes responding to oestrus synchronization. A similar response has been observed in studies conducted during the breeding season with progestagens/progesterone (P4; Fleisch et al, 2012;Fierro et al, 2016;Zonturlu et al, 2018), which was possibly due to the efficient delivery of P4 by the controlled internal drug release (CIDR) device during the treatment period (Abecia et al, 2012). The tight synchrony of oestrus observed at 36 and 48 h post CIDR withdrawal in the present study was also reported by other researchers (Vilarino et al, 2013;Swelum et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Progesterone/progestagens are often combined with equine chorionic gonadotropin (eCG) at device withdrawal in a protocol (Donovan et al, 2004;Zonturlu et al, 2018;Martinez-Ros et al, 2019). Moreover, reports both in small ruminants (Bodin et al, 1997;Drion et al, 2002;Anel et al, 2005) and in cattle (Drion et al, 2001) indicate that when eCG is used, fertility is lower with each breeding, due to accumulation of residual antibodies from previous treatments (Bodin et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…and enhanced pregnancy rate and litter size (Hashem, El‐Azrak, Nour El‐Din, Taha, & Salem, 2015; Zonturlu et al., 2018). High pregnancy rates with natural mating were reported after treatment including GnRH injection at device insertion of progesterone during the out of breeding season (Martinez et al., 2015).…”
Section: Introductionmentioning
confidence: 99%